MITIGATING STRATEGIES OF THREATS TO QUANTITY SURVEYING PROFESSION IN THE NIGERIAN CONSTRUCTION INDUSTRY - Lekan Ojo; Bolarinwa Ibrahim; Ayodeji Oke; Akinsanmi Akindeinde (Journal of Construction Project Management and Innovation)
Quantity surveying (QS) profession had faced numerous challenges in recent decades than when it was first introduced in developing countries. In addition, opportunities via technology advancement to the profession were also perceived as threats. This, therefore, inform the need to investigate the possible mitigating strategies to the threats confronting the profession in the Nigerian construction industry as an attempt to proffer solutions. Therefore, opinions of quantity surveyors in construction firms, consulting firms and government establishments of Lagos State, Nigeria were collected through a survey. The mitigating strategies garnered from extant literature were used to elicit the opinions of the respondents. One hundred and twelve (112) copies of questionnaires were administered, while the retrieved copies were used to analyse with both descriptive and inferential statistics. Mean score and Standard Deviation (SD) were used to rank the opinions of the respondents, and factor analysis was used to group the mitigating strategies into concise form for ease of discussion. The results of the analysis show that the mitigating strategies identified in the study are significant to mitigating the threats in the QS profession. The factor analysis conducted grouped the mitigating strategies into four major groups, namely practice, knowledge, progressive learning and ethics. These groupings were discussed within the context of the study and in relation with previous researches. This study proffers possible solutions to the threats to the QS profession that had been publicised in many studies.